Defining subjectivity in visual art audio description - Soler Gallego, Silvia (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
Audio description is an intersemiotic translation modality used to make art museums accessible to visually impaired visitors. Existing audio description guidelines in various countries recommend describing only that which is seen, in other words, to avoid subjective interpretations of the visual message. However, there is evidence that some visually impaired people prefer more subjective audio descriptions. The controversy around this issue has generated reception- and product-oriented studies of audio description which demonstrate that not only is subjectivity present in existing audio descriptions, but also that it may benefit the construction of a more meaningful experience. A methodology which combines corpus and contextual analysis and draws on cognitive linguistics as well as art theories has been followed in this study to examine audio descriptive guides in art museums in four different countries. Results show considerable levels of subjectivity and offer a categorization of this element. Additionally, the level and type of subjectivity appear to be influenced by contextual factors, including the level of abstraction of the artwork and the audio describer’s degree of compliance with existing guidelines.